Oral mite anaphylaxis after ingestion of Korean pancake. (2020) - Senba, Seitaro; Tsuji, Takao; Kikuchi, Ryota; Iwai, Yuki; Kawagoe, Junichiro; Nakamura, Hirouki; Aoshiba, Kazutetsu
Abstract: Background: Oral mite anaphylaxis (OMA) is a syndrome characterized by severe allergic manifestations occurring in atopic patients shortly after the intake of foods made with mite-contaminated wheat flour. A history of atopic disease has been identified as one of risk factors for the development of OMA. This is the report that OMA was induced by the ingestion of Korean pancake prepared with commercial mixed wheat flour contaminated with mites. Case presentation: A 15-year-old Japanese girl with a history of atopic asthma and dermatitis was admitted to the emergency department with the anaphylactic symptoms of urticaria, skin flushing, throat discomfort, acute dyspnea and severe wheezing that developed shortly after the ingestion of home-cooked buchimgae (Korean pancake) prepared with commercial mixed wheat flour. The ingredients in the buchimgae were eggs, shrimps and chopped Chinese chives, but the girl had previously consumed these individual ingredients without incident. Microscopic examination of the mixed wheat flour revealed the presence of large numbers of live dust mites. The patient's serum specific IgE analysis was positive for antibodies to dust mite allergens. From these findings, the anaphylactic episode in this patient was concluded to be the result of ingestion of mixed wheat flour contaminated with mites. Conclusions: OMA was induced by the ingestion of wheat flour contaminated with mites. Physicians should be aware of this clinical picture, particularly in the case with risk factors, and recommend that wheat flour should be stored in a refrigerator to prevent mite proliferation and the development of OMA. Highlights: Oral mite anaphylaxis (OMA) is a syndrome characterized occurring after the intake of foods made with mite-contaminated wheat flour.